Why and how to integrate liquidity risk into a VaR-framework - Sebastian Stange; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
We integrate liquidity risk measured by the weighted spread into a Value-at-Risk (VaR) framework. The weighted spread measure extracts liquidity costs by order size from the limit order book. We show that it is precise from a risk perspective in a wide range of clearly defined situations. Using a unique, representative data set provided by Deutsche Boerse AG, we find liquidity risk to increase traditionally-measured price risk by over 25%, even at standard 10-day horizons and for liquid DAX stocks. We also show that the common approach of simply adding liquidity risk to price risk substantially overestimates total risk because correlation between liquidity and price is neglected. Our results are robust with respect to changes in risk measure, to sample periods and to effects of portfolio diversification.
Keywords: G11; G12; G18; G32; 330; asset liquidity; price impact; weighted spread; Xetra Liquidity Measure (XLM); Value-at-Risk; market liquidity risk; Wertpapierhandel; Börsenkurs; Risikomaß; Marktrisiko